PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN BUDAYA TRI HITA KARANA TERHADAP KINERJA MANAJERIAL LEMBAGA PERKREDITAN DESA (LPD) - I Nyoman Raditya Suparsabawa; Ketut Tanti Kustina (Jurnal Riset Akuntansi (JUARA), 2018)
This study aims to determine the effect of the implementation of good corporate governance andculture tri hita karana to managerial performance in nine Lembaga Perkreditan Desa (LPD) inNorth Kuta District. Types of data used in this study are primary and secondary data. Sampledetermination technique used in this research is saturated sampling technique by using questionnaire. The data testing technique used multiple linear regression with the first classicalassumption test consisting of normality test, multicolinearity test, and heteroscedasticity test.The results showed that the principles of good corporate governance (X1) and tri hita karana culture(X2) had a significant positive effect on LPD Managerial Performance in North Kuta District.Good corporate governance has important principles that must be implemented in each agencyas one form of corporate governance towards achieving a succession of agencies and gain highconfidence. Each value of the philosophy of tri hita karana must be a guideline to form a mentalattitude, work ethic and character of human resources noble character so that it can change theperformance of Lembaga Perkreditan Desa (LPD) grow better and gain public confidence. It issuggested that LPD in South Kuta Subdistrict and in Bali can make the principles of good corporategovernance and culture of tri hita karana as work guidance in LPD management.